Kitten crowd - Daniels, Lucy (Hodder Children's Books London, 1996)
Mandy, who loves trying to solve her friends' pet problems, promises to help Sarah find homes for her cat's six baby kittens before she moves house. Just as Mandy thinks she has found the perfect place - a local old people's home whose residents need cheering up - the kittens go missing